The Future of the World Social Forum: The work of translation - BOAVENTURA DE SOUSA SANTOS (Development, 2005, 48(2) (15-22), 2005)
Boaventura de Sousa Santos argues that the WSF is the first large international progressive movement following the neoliberal backlash in the early 1980s. The WSF holds out the hope that another world is possible but while the WSF reveals the diversity of social struggles fighting against neo-liberal globalization all over theworld call it calls for a giant work of translation. On the one hand, there are local movements and organizations that are very different in their practices and objectives and embedded in different cultures. On the other, there are transnational organizations, from the South and the North, that differ widely among themselves. He asks how tobuild articulation, aggregation and coalition among these different movements and organizations? And proposes translation as the alternative to general theory